2019
DOI: 10.17323/1814-9545-2019-3-101-129
|View full text |Cite
|
Sign up to set email alerts
|

Academic Dishonesty among College Students: Academic Motivation vs Contextual Factors

Abstract: Academic dishonesty among college students is often associated with low academic motivation, which has been confirmed by multiple international findings. However, the role of academic motivation may be overestimated, as such studies do not normally control for contextual factors such as faculty and peer behavior. This study utilized the theoretical framework of Eric M. Anderman and Tamera B. Murdock to identify the factors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…The study utilized a validated researcher-made questionnaire on Academic cheating. This is composed of thirty (30) items on the common misconducts done by the students in their academics. Each category includes statements of common misdemeanors of students in exams, assignments, and bibliography.…”
Section: Methodsmentioning
confidence: 99%
“…The study utilized a validated researcher-made questionnaire on Academic cheating. This is composed of thirty (30) items on the common misconducts done by the students in their academics. Each category includes statements of common misdemeanors of students in exams, assignments, and bibliography.…”
Section: Methodsmentioning
confidence: 99%
“…Tingkat motivasi otonom yang lebih tinggi dapat ditingkatkan dengan memenuhi tiga aspek psikologis dasar, yaitu, otonomi, kompetensi, dan hubungan sosial. Otonomi merujuk pada persepsi untuk merasa berdaya dan memiliki kebebasan untuk membuat pilihan (Shmeleva & Semenova, 2019). Kompetensi melibatkan perasaan mampu dan efektif dalam usaha seseorang.…”
Section: Pendahuluanunclassified
“…Shmeleva (2016) also conducted a study of the factors and conditions that influence the occurrence and spread of academic fraud among students. Later, together with Shmeleva and Semenova (2019), they studied the factors that determine the possibility of academic fraud. They noted the fact that this phenomenon is often associated with the low level of study motivation, which is confirmed by a number of Russian and foreign studies.…”
Section: Problem Statementmentioning
confidence: 99%